A qualitative analysis of educational, professional and socio-cultural issues affecting interprofessional collaboration in oncology palliative care. Issue 9 (September 2022) - Bennardi, Marco; Diviani, Nicola; Saletti, Piercarlo; Gamondi, Claudia; Stüssi, Georg; Cinesi, Ivan; Rubinelli, Sara
Abstract: Objectives: Oncology palliative care (PC) services seek to improve quality of life in patients with cancer. PC providers face significant systemic obstacles, stemming from insufficient collaboration between healthcare providers. This study explores these obstacles and strategies to help facilitate successful collaboration amongst healthcare providers at a systemic level. Methods: A multicenter qualitative study was conducted via interviews and focus groups. Fifty employees in Italian-speaking Switzerland were interviewed, along with ten relatives of oncology patients. Framework analysis was used to identify and categorize the most prominent themes. Results: Three main themes were identified: knowledge of and connection to other healthcare approaches; beliefs, attitudes and behavior regarding collaboration; and values, attitudes and beliefs towards life, end-of-life and optimal care approaches for oncology patients. Conclusions: Strategies that promote interprofessional collaboration and oncology PC services should foster a cultural shift towards perceiving these services as a medical specialty, thereby contributing to quality patient care. Implications: An overview of potential limitations is provided, in addition to a timeline of interprofessional collaboration which would help to optimize oncology PC services. Highlights: Oncology palliative care utilization is suboptimal. Poor collaboration between healthcare professionals contributes to underutilization of palliative care. Various types of education (formal, informal, non-formal) for healthcare professionals may improve collaboration. A cultural shift towards favoring collaboration may help overcome the silo structure of healthcare disciplines.